Investigating and Prioritizing the Factors Affecting Levels of Learning Technology in the Enterprise (Empirical Evidence of Isfahan Enterprises) - Mehdi Elyasi; Hossein Khosropour; Narges Rahimian; Mohammad Ebrahim Sadeghi; Hamed Nozari (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Value creation through technology learning at the corporation level has been remarkable in recent years because three essential reasons for paying attention to wealth-making subjects, development of technological abilities, and creating competitive advantage have been converted to the strategic topics of corporations. This research aims to define and prioritize the factors affecting technology learning levels at the Isfahan state corporation level.Methodology: The statistical population of 104 corporations active in the industrial context examines the quintet assumptions by accumulating needed data using a questionnaire with standard components and a reliability coefficient of 0.845.Findings: Regarding the results, it is demonstrated that four studied levels in a structural equations model have indeed explained technological learning levels at the Isfahan state corporations level, and each one has been effective straight on the mentioned process. Accordingly, the straightest effectiveness related to the average level (0.78), basic level (0.67), and global level (0.65) are respectively in the following degrees of importance, and each of these affective factors on these levels has been discussed.Originality/Value: The study recommends that managers improve the levels of technology learning at the enterprise level and pay attention to the identified factors to understand them.